2017
DOI: 10.1007/s10295-017-1978-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial healing of cracks in concrete: a review

Abstract: Concrete is the most widely used construction material of the world and maintaining concrete structures from premature deterioration is proving to be a great challenge. Early age formation of micro-cracking in concrete structure severely affects the serviceability leading to high cost of maintenance. Apart from conventional methods of repairing cracks with sealants or treating the concrete with adhesive chemicals to prevent the cracks from widening, a microbial crack-healing approach has shown promising result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(58 citation statements)
references
References 82 publications
0
57
0
1
Order By: Relevance
“…Sporosarcina pasteurii (also named Bacillus pasteurii ), Sporosarcina ureae , Bacillus sphaericus , and Bacillus megaterium belong to this group. They have been used in a number of studies for waterproofing and improving strength and durability aspects of porous and cracked concrete, as reviewed in 2010 by De Muynck et al, in 2013 by Pacheco‐Torgal and Labrincha, Phillips et al and Van Tittelboom and De Belie, in 2014 by Sarayu et al, in 2015 by Wong, and recently in 2017 by Joshi et al, Vijay et al, Souradeep et al, Han and Xing, and exhaustively by Al‐Salloum et al, (the latter review covering 255 literature references) and several recent reports …”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…Sporosarcina pasteurii (also named Bacillus pasteurii ), Sporosarcina ureae , Bacillus sphaericus , and Bacillus megaterium belong to this group. They have been used in a number of studies for waterproofing and improving strength and durability aspects of porous and cracked concrete, as reviewed in 2010 by De Muynck et al, in 2013 by Pacheco‐Torgal and Labrincha, Phillips et al and Van Tittelboom and De Belie, in 2014 by Sarayu et al, in 2015 by Wong, and recently in 2017 by Joshi et al, Vijay et al, Souradeep et al, Han and Xing, and exhaustively by Al‐Salloum et al, (the latter review covering 255 literature references) and several recent reports …”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…Due to physicochemical properties of EPSs, biofilms can behave as viscous liquids to resist the flow-induced shear stress, and substantially plug the pore (Costerton et al, 1995;Flemming et al, 2011;Rozen et al, 2001;Stoodley et al, 1999;Tsai, 2005). Engineering bioplugging processes need to control biofilms selectively and substantially growing in desired places (Abdel Aal et al, 2010;Cuzman et al, 2015;Joshi et al, 2017). Therefore, mechanisms on biofilm development and its adhesive strength with solids surface is vitally important.…”
Section: Introductionmentioning
confidence: 99%
“…Limestone, or calcium carbonate, is a concrete compatible material that is perfectly suitable for sealing (waterproofing) of cracks in concrete. Several research groups worldwide have developed bacteria-based healing agents to enhance the self-healing capacity of cement pasts, mortars and concrete [7][8][9][10][11][12]. Pioneering and lab-based research by the Delft research group has shown that lactate-based organic compounds like calcium lactate and lactide-polymers) are suitable carbon sources for the bacteria and that these compounds are furthermore concrete compatible in the sense that they as additive, within limits, do not negatively affect strength development of concrete [7, 8 13,14].…”
Section: Autonomous Crack Repair By Limestoneforming Bacteriamentioning
confidence: 99%